2017
DOI: 10.1093/icesjms/fsx162
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of the autodiametric method for estimating fecundity of Reinhardtius hippoglossoides, a species with an unusual oocyte development strategy

Abstract: The autodiametric method is a highly streamlined method for estimating fecundity of fish with determinate oocyte development pattern. Greenland halibut presents a peculiar reproductive strategy with two simultaneously cohorts one of large vitellogenic oocytes (for the current year) and another one of small vitellogenic oocytes (for the subsequent year). Results of this study showed that autodiametric method can be applied to estimate fecundity in Greenland halibut. Additionally, spatial differences in the auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…0.778 than 6.5% in oocyte density estimated with different calibration curves for two cod stocks, concluding that they were essentially the same curve. The use of OPD and the success of the autodiametric method could vary between areas, stocks and species (Dominguez-Petit et al 2018)spatial differences in the autodiametric calibration curve were observed in the Northwest Atlantic, but did not translate into differences in fecundity at length. This is the first time that spatial differences between ACCs of the same species have been reported, what could be the result of (i, for reasons such as energy allocation and preservation techniques (Friedland et al 2005).Thus, fecundity estimations could be inaccurate when published calibra-tion curves not estimated for the species or a stock of interest are used (Witthames et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…0.778 than 6.5% in oocyte density estimated with different calibration curves for two cod stocks, concluding that they were essentially the same curve. The use of OPD and the success of the autodiametric method could vary between areas, stocks and species (Dominguez-Petit et al 2018)spatial differences in the autodiametric calibration curve were observed in the Northwest Atlantic, but did not translate into differences in fecundity at length. This is the first time that spatial differences between ACCs of the same species have been reported, what could be the result of (i, for reasons such as energy allocation and preservation techniques (Friedland et al 2005).Thus, fecundity estimations could be inaccurate when published calibra-tion curves not estimated for the species or a stock of interest are used (Witthames et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the hiatus limit method, the autodiametric method 12 utilises changes in the mean size, SD and skewness of VO OSFDs to track individual reproductive development over time. However, the main purpose of this frequently used, fully automatic method, is to estimate individual fecundity prior to spawning by relating mean VO size with the corresponding oocyte packing density (OPD) 13 . The proper establishment of this calibration curve requires ovarian homogeneity, which is typically seen in pre-spawners but not in spawners, where ovulated oocytes congregate in the ovarian lumen before egg release (e.g.…”
mentioning
confidence: 99%
“…sole, Solea solea 14 ). So, despite the notation that the autodiametric method also works on species showing complex OSFDs, such as VO bimodality in pre-spawning Reinhardtius hipploglossoides 13 , it is not intended for examination of spawning ovaries. Alternatively, the historic 'stage of spawning method' is designed for use during spawning and uses VO SD as criterion 15 but encounters similar problems to the above-mentioned hiatus limit method.…”
mentioning
confidence: 99%